The Role of Patient Experience in Improving Revisit Intention Among General Outpatients in District Hospital - Hans Yurian Effendy; Aprilita Rina Yanti; Intan Silviana Mustikawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
In response to the evolving landscape of public healthcare services, hospitals are expected not only to maintain operational efficiency but also to adapt to the shifting needs and expectations of patients as healthcare consumers. The presence of non-BPJS patients in regional public hospitals plays a strategic role not only contributing to revenue diversification but also reflecting service quality, institutional competitiveness, and shaping public perception. The declining trend in outpatient visits by general patients at RSUD Balaraja over the past three years highlights the need to understand the factors influencing consumer behavior in determining revisit intentions. This study examines the effect of co-creation and hospital image on the revisit intention of outpatient general patients at RSUD Balaraja, with patient experience as a mediating variable. The research employed a quantitative explanatory design involving 278 outpatient general patients selected through purposive sampling. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that patient experience plays a significant mediating role in shaping revisit intention among general outpatients at RSUD Balaraja. These findings confirm that patient experience serves as a central factor in post-service evaluation processes, which ultimately drive patients’ intention to return. Therefore, hospitals need to enhance patient involvement in service processes (co-creation), improve public perception of institutional image (hospital image), and develop patient-centered service systems as a key strategy to increase revisit intention among general outpatients.